Urban heat island intensity and its mitigation strategies in the fast-growing urban area - Shweta Jain; Srikanta Sannigrahi; Somnath Sen; Sandeep Bhatt; Suman Chakraborti; Shahid Rahmat (Journal of Urban Management, 2020)
Climate change especially rising temperature in the urban areas has become a major focus of attention worldwide because of the impacts having on human beings, biodiversity, and urban ecosystem. Time series Landsat (TM and ETM+) satellite data products have been employed in this study to quantify the spatiotemporal Land Surface Temperature (LST) and Urban Heat Island (UHI) intensity for the year of 2000, 2005, 2010 and 2015, respectively. Biophysical characteristics of the city have been assessed through Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI) and Normalized Difference Bareness Index (NDBaI). The thermal behavior of the city varied distinctly. Seasonal LST and biophysical composition of the city has been analyzed to explore the temperature and greenness sensitivity across the city region. The per capita electricity consumption of the city was positively correlated with the surface LST for both summer and autumn/spring season. A relative brightness temperature approach was employed to examine the nature of UHI across the city. It is evident from the observation that the temperature is very high within the city core as well as certain surrounding areas of the city, especially on the southern side. The temperature is comparatively lower on the western side of the city than the eastern region. Certain peripheral regions, however, show a higher temperature. This can be due to the development taking place in the outer areas of the city and destruction of vegetation in the outlying parts of the city. Studied NDVI indicates that vegetation in the city is not balanced. It is high in the western part which maybe because of the locations of different academic institutions, botanical gardens, seminary hills, agricultural land, etc. Whereas, the eastern part is devoid of vegetation. Also, the areas in the periphery, especially near the airport and Ambajhari Lake, has very low vegetation. The bareness is also high in the peripheral regions. Result also shows that street-based heat intensity mitigation helps for urban planning.
Keywords: 710; Biodiversity; Land surface temperature; Nagpur; NDVI; Remote sensing; Urban heat island intensity